Upaya Meningkatkan Keterampilan Menulis Deskripsi Dengan Menggunakan Metode Tanya Jawab Berbantuan Media Gambar Berseri Pada Peserta Didik Kelas IV-A Di SDN 8 Menteng Palangka Raya - Yuli Limbong Datu; Nyoto Nyoto; Diplan Diplan; FX Manesa (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
The research background in learning Indonesia include aspects of listening, speaking, reading, writing. Writing skill as one of the four language skills has a very important role in human life. This study aims to improve the ability to write descriptions in class IV A students at SD Negeri 8 Menteng Palangka Raya and describe the activities of students during learning to write descriptions using the question and answer method assisted by serial picture media to students in class IV A SD Negeri 8 Menteng Palangka Raya . This research uses the Classroom Action Research (CAR) using the question and answer method. The population of this research is SDN 8 Menteng Palangka Raya. The sample of the research is 33 students of Class IV A of SDN 8 Menteng Palangka Raya. The results of this research are improving writing descriptions can be seen from the average score of students during the pretest, namely 65.60. The results of the first cycle of post test writing descriptions get an average of 71.65. while the results of the post test cycle II writing a description get an average of 80.17. increase in the average value of cycles I and II of 8.52. The classical completeness in cycle I was 63.63% and Cycle II was 93.93%.